Technology-based learning innovation to enhance Student creativity: a literature review - Munandar, Nilam Cahya; Humairo, Tasya; Al-Sheikh, Fatima (Journal of Loomingulisus ja Innovatsioon, 2026)
Rapid advancements in the 21st-century education landscape necessitate the integration of digital tools to foster higher-order thinking skills, particularly in the complex domain of science. This study aims to analyze the effectiveness of technology-based learning innovations in enhancing student creativity within physics education through a comprehensive literature review. Data were collected from reputable international journals published between 2019 and 2024, utilizing a systematic screening process to identify relevant empirical studies regarding digital interventions. The analysis reveals that specific innovations, such as augmented reality, virtual laboratories, and interactive simulations, significantly improve students’ creative thinking abilities by visualizing abstract physical phenomena and allowing for open-ended experimentation without physical constraints. Unlike previous reviews that focus primarily on cognitive learning outcomes or conceptual mastery, this research uniquely synthesizes how digital platforms specifically target indicators of creativity, including fluency, flexibility, and elaboration in solving physics problems. These findings offer critical theoretical and practical implications for curriculum developers and physics educators to design technology-integrated learning environments that not only transfer knowledge but also cultivate the inventive scientific mindset required for the future development of physics.